1982
DOI: 10.1051/rnd:19820306
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine, triiodothyronine and iodide in different breeds of newborn calves

Abstract: Summary. Plasma thyroxine (T 4 ), triiodothyronine (T 3 ) and iodide levels were measured from birth until 30 days of age in 17 Holstein x Friesian (HF), 7 Salers and 7 Charolais calves born at term. The response of plasma T 4 and T 3 levels to bovine thyrotropin (TSH) injection was also compared in two groups of 9 HF calves 3hrs and 21 days, respectively, after birth.In the HF calves, plasma T 4 and T 3 levels increased from birth to 6 hrs (when the rectal temperature of these calves decreased slightly), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 12 publications
(13 reference statements)
4
19
0
Order By: Relevance
“…This may be because not enough samples were studied or that they were not collected at the exact postpartum time when the transient rise occurred. On the contrary, the frequent and precise sampling practiced by Davicco et al (1982) (Balsam and Ingbar, 1979 ;Kaplan and Utiger, 1978 ;Naito et al, 1981) and piglets (Slebodzinski et al, 1982), has been shown to result in a decrease of circulating T3 in these species (Chopra, 1980 ;Hastings and Zeman, 1979 ;Heinen et al, 1981 andSlebodzinski et al, 1982, respectively) ; this phenomenon has also been shown in humans (Azizi, 1978 ;Burman et al, 1979 ;Suda et al, 1978), adult sheep (Blum et al, 1980), growing bulls Tveit and Almlid, 1980), deer (Bahnak et al, 1981), chickens (May, 1978) …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This may be because not enough samples were studied or that they were not collected at the exact postpartum time when the transient rise occurred. On the contrary, the frequent and precise sampling practiced by Davicco et al (1982) (Balsam and Ingbar, 1979 ;Kaplan and Utiger, 1978 ;Naito et al, 1981) and piglets (Slebodzinski et al, 1982), has been shown to result in a decrease of circulating T3 in these species (Chopra, 1980 ;Hastings and Zeman, 1979 ;Heinen et al, 1981 andSlebodzinski et al, 1982, respectively) ; this phenomenon has also been shown in humans (Azizi, 1978 ;Burman et al, 1979 ;Suda et al, 1978), adult sheep (Blum et al, 1980), growing bulls Tveit and Almlid, 1980), deer (Bahnak et al, 1981), chickens (May, 1978) …”
Section: Introductionmentioning
confidence: 97%
“…The subsequent profile depended on the diet ( fig. 1 ) (Cabello and Michel, 1974 ;Davicco et al, 1982 ;Kahl et al, 1977 ;Nathanielsz and Thomas, 1973). However, all of them, except Davicco et al (1982) found that the blood sampling closest to birth gave the maximal plasma T4 level.…”
Section: Introductionmentioning
confidence: 99%
“…The thyroid function prior to birth strongly interferes with cardiovascular and lung adaptation, as well as with thermogenesis in the newborn lamb [51]. At birth T 3 and T 4 levels are high [23,43] and increase during the fi rst hours of life due to both cortisol surge which supports the maturation of the thyroid axis and increased TSH secretion [52]. This peak in thyroid hormone concentration at birth considerably increases heat production and regulates cold thermogenesis.…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…However, it was one-fifth of that reported in newborn lambs (Davicco et al, 1980) and in newborn calves (Davicco et al, 1982) Vigouroux (1976) was used, where I is separated from organic-bound I by perchloric acid protein precipitation. In our method, unbound thyroxine was removed from the plasma by ion― exchange chromatography (Aumont and Tressol, 1987).…”
Section: Analysesmentioning
confidence: 88%